PENGUKURAN TINGKAT KEMATANGAN PENYELARASAN STRATEGI TEKNOLOGI INFORMASI TERHADAP STRATEGI BISNIS ANALISIS MENGGUNAKAN FRAMEWORK COBIT 4.1 (Studi Kasus PT. BRI, Tbk) - Adityawarman, Adityawarman (JURNAL AKUNTANSI DAN AUDITING, 2012)
Strategic alignment between Information Technology (IT) and business has become CIOs andCEOs primary concern nowadays. This shows that strategic alignment is needed to achievebusiness goals. Every function in organization have their own strategies in achieving there goal,these strategies should fit each other and aligned. The same thing should happen in the strategiesof IT in organization, IT strategy should in harmony with business strategy. One of the mainissues for the next step is how to asses the maturity level of strategic alignment. By knowing thestrategic alignment level, organization should be able to identify its current position, and decidewhat practices shoud perform in order to achieve continuous improvement. The assessment ofstrategic alignment maturity level as a tool for assessing alignment level of IT strategy withbusiness strategy. This research assesses maturity alignment level of IT strategy with businessstrategy at PT. Bank BRI, Tbk, using IT Strategic Plan 2003–2008 as a framework and usingCOBIT 4.1 maturity model for assessment. Result of this research shows that level of maturityalignment of IT strategy with business strategy approaching defined level at 2.90 score. The resultshows that procedures have been standardized and documented, and communicated throughtraining. It is mandated that these processes should be followed. However, it is unlikely thatdeviations will be detected. The procedures themselves are not sophisticated but are theformalization of existing practices.Keywords:business, IT strategic alignment, COBIT 4.1 maturity model, IT balance scorecard, strategicalignment measurement, maturity measurement.